The Effects of Puerarin on Autophagy Through Regulating of the PERK/eIF2α/ATF4 Signaling Pathway Influences Renal Function in Diabetic Nephropathy - Xu X (Dove Medical Press, 2020)
Xiaohui Xu,1,2,* Biao Chen,3,* Qichun Huang,1 Yani Wu,4 Tao Liang5 1Department of Pharmacy, Affiliated Tumor Hospital of Guangxi Medical University, Nanning, Guangxi 530021, People’s Republic of China; 2Institute of Cancer Prevention and Treatment of Guangxi Zhuang Autonomous Region, Nanning, Guangxi 530021, People’s Republic of China; 3The First Nanning People’s Hospital, Nanning, Guangxi 530022, People’s Republic of China; 4Pharmaceutical College, Guangxi Medical University, Nanning, Guangxi 530021, People’s Republic of China; 5College of Stomatology of Guangxi Medical University, Nanning, Guangxi 530021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaohui XuDepartment of Pharmacy, Affiliated Tumor Hospital of Guangxi Medical University, No. 71, Hedi Road, Nanning 530021, People’s Republic of ChinaTel/ Fax +86 771-5778582Email 1056112307@qq.comTao LiangCollege of Stomatology of Guangxi Medical University, No. 10, Shuangyong Road, Nanning 530021, People’s Republic of ChinaTel/ Fax +86 771-5358635Email kqliangtao@126.comBackground and Purpose: Autophagy is the main protective mechanism against aging in podocytes, which are terminally differentiated cells that have a very limited capacity for mitosis and self-renewal. Here, a streptozotocin-induced DN C57BL/6 mouse model was used to investigate the effects of puerarin on the modulation of autophagy under conditions associated with endoplasmic reticulum stress (ERS). In addition, this study aimed to identify the potential underlying molecular mechanisms.Methods and Results: DN C57BL/6 mouse model was induced by streptozotocin (150 mg/kg) injection. The mice were administered rapamycin and puerarin, respectively, daily for up to 8 weeks. After the serum and kidney samples were collected, the fasting blood glucose (FBG), parameters of renal function, histomorphology, and the podocyte functional proteins were analyzed. Moreover, the autophagy markers and the expressions of PERK/ATF4 pathway were studied in kidney. Results found that the FBG level in DN mice was significantly higher than in normal mice. Compared with DN model mice, puerarin-treated mice showed an increased expression of podocyte functional proteins, including nephrin, podocin, and podocalyxin. Furthermore, the pathology and structure alterations were improved by treatment with rapamycin and puerarin compared with the DN control. The results indicated an elevated level of autophagy in rapamycin and puerarin groups compared with the DN model, as demonstrated by the upregulated expression of autophagy markers Beclin-1, LC3II, and Atg5, and downregulated p62 expression. In addition, the levels of PERK, eIF2α, and ATF4 were reduced in the DN model, which was partially, but significantly, prevented by rapamycin and puerarin.Conclusion: This study emphasizes the renal-protective effects of puerarin in DN mice, particularly in the modulation of autophagy under ERS conditions, which may be associated with activation of the PERK/eIF2α/ATF4 signaling pathway. Therefore, PERK may be a potential target for DN treatment.Keywords: diabetic nephropathy, autophagy, PERK, puerarin